The stories clothes tell voices of working-class Japan - Horikiri, Tatsuichi 1925-; Wagoner, Rieko (Lanham Rowman & Littlefield, 2016)
"This compelling social history tells the stories of ordinary people in modern Japan. Tatsuichi Horikiri spent a lifetime searching out old items of clothing and oral history accounts to shed light on those who used these items. He reveals not only the often desperate lives of these people, he illuminates their hopes, aspirations, and human values"--Provided by publisher.
"Spanning decades of research, this compelling social history tells the stories of ordinary people in modern Japan. Tatsuichi Horikiri spent a lifetime searching out old items of clothing--ranging from everyday kimono, work clothes, uniforms, and futons to actors' costumes, diapers, hats, aprons, and bags. Simultaneously he collected oral history accounts to shed light on those who used these items. Horikiri reveals not only the difficult and sometimes desperate lives of these people, most from the lower strata in early twentieth-century Japan, he illuminates their hopes, aspirations, and human values. He also explores such topics as textile techniques, the history of fashion, and the ethnography of clothing and related cultural phenomena. Having been wrongly accused and tortured by the Japanese military police in China during World War II, Horikiri takes a deeply empathetic view of all those who struggle--from peasants and coal miners to traveling salesmen and itinerant performers. This personal connection sets his account apart, giving his writing great power and immediacy. Students and scholars of Japanese history, as well those interested in material culture, labor history, and feminist history, will find this book deeply illuminating".
Notes to the Reader: Era Designation and Timeline -- Map -- Kasuri Mattress Cover from Home -- Koshimaki petticoat of 83 patches -- Echigo-jishi Costume for Boy Dancer -- How Many Diapers? -- Two Hanten Field Jackets -- Okiboda, the Pride of Women -- My Teacher's Sunday Best -- A Weighty Quilt -- Life with a Mosquito Net -- A Bed of Wood Shavings -- The Meisen the Girl Could Not Wear -- Dead Horse -- Female Coal Miners -- Aunties and Uncles -- Rich and Poor -- A Begging Girl -- Noble-minded Ladies -- A Gown of Leaves for the Dead -- Katatsuke-gasuri -- A Lady in a Dilapidated Mansion -- Female Workers in Textile Mills -- Forbidden Tears -- The Thousand-stitch Waistband -- The Rising Sun Kimono That She Wore -- Gifts from My Mother -- Akemi's Song -- Military Uniforms and Shoes -- What Mompe Trousers Symbolized -- A White Chima Jeogori -- Sarasa Print Bed Quilt -- Hanten Story -- Afterword -- Clothing Term Glossary.
First published in 1990 as a monograph, Nuno no Inochi (The Life of Clothes) by Tokyo publisher Shinnippon Shuppan-sha; a new and expanded edition was brought out by Shinkagaku Shuppan-sha in 2004; the present volume is a translation of the 2004 edition.
Includes bibliographical references and index.
In English and Japanese.
Keywords: Costume -- Japan -- History; Clothing and dress -- Japan -- History; Working class -- Clothing -- Japan -- History; Working class -- Japan -- Biography; Oral history -- Japan; Japan -- Social life and customs; Japan -- Social conditions; Japan -- Biography